The challenges and opportunities in ESG integration in investment activities for private equity firms/funds in South Africa - Dube, Cuma Velile (Rhodes University, Faculty of Commerce, Rhodes Business School)
Responsible Investing (RI) is an investment strategy that considers not only the economic but also the environmental, social and governance (ESG) issues in the investment analysis and post-investment activities. The consideration of ESG issues is aimed at generating long-term risk-adjusted financial returns and a positive social and environmental impact. This research seeks to contribute to the study of responsible investment (RI), as it relates to private equity investments, an area not well researched. This research also seeks to contribute to the academic literature on responsible institutional investment in South Africa; the opportunities it presents to optimise portfolios, as well as the means with which the challenges faced in integrating ESG factors in investment activities may be overcome. More specifically, the challenges and opportunities for the integration of ESG factors in the investment process were investigated through the experiences of a small sample of South African private equity firms. The sample of private equity firms that participated in this research are signatories of the United Nations Principles of Responsible Investing (UNPRI). Representatives of the participating firms were interviewed in line with the qualitative research design and the post-positivist paradigm of this research. The research design and paradigm are chosen to explore the experiences of practitioners in their integration of ESG issues in the investment process. This research shows that the challenges to ESG integration for the private equity firms considered have remained largely consistent over the last ten years. The challenges include industry skills and knowledge gap and the lack of reliable and comparable ESG data at the portfolio company level. The Opportunities presented, by adopting responsible investing as an investment strategy, are rooted in protecting the downside (risk management) and in finding new value creation opportunities. In summary, it was found that the participating firms continue to face significant capacity challenges in overcoming the challenges to mainstreaming ESG in investment processes. Further research may explore whether the challenges and opportunities that persist from the findings of this research are pervasive throughout the entire sector and whether innovative ways have been found to overcome the challenges have been found by private equity firms that are not signatories of the UNPRI.
Keywords: Social responsibility of business -- South Africa; Investments Moral and ethical aspects -- South Africa; Private equity -- South Africa; Investments Environmental aspects -- South Africa; Investments Social aspects -- South Africa; Investments Law and legislation -- South Africa; United Nations Principles of Responsible Investing (UNPRI)